Modelling of a Hybrid Solar Micro-Gas Turbine fuelled by biomass from agriculture product - Maria Cristina Cameretti (Energy Reports, 2020)
Sustainable biomass exploitation for combined heat and power (CHP) generation is fundamental to address concerns about climate changes related to energy conversion systems. The aim of the work is to design a power plant able to satisfy energy demands exclusively through renewable resources. A layout of a hybrid micro-gas turbine-solarplant fed by biomass from agriculture products (olive pits) is modelled. It provides the coupling between a gasifier, dedicated to the biomass conversion and a micro gas turbine, optimized for the operation with syngas. In particular, the MGT plant is integrated with a solar tower field, able to provide a partial or complete fuel heating replacement depending on the amount of solar heat provided to the working fluid reaching the turbine inlet temperature. After the solar field design able to reduce fuel consumption during diurnal hours, a gasifier was integrated to obtain a syngas from biomass in place of the traditional natural gas. A parametric analysis aimed to define the gasifier parameters is reported and allowed to obtain a syngas able to satisfy the power demands of the MGT with good performances. The Thermoflex® commercial software is used to model the full plant. The results in terms of efficiency and environmental impact are reported and compared to those obtained with the traditional natural gas-fuelled MGT.
Keywords: 330; Biomass; Gasification; Micro gas turbine; Solar energy; Syngas